The relevance of using accounting fundamentals in the Mexican stock market - Dorantes Dosamantes, Carlos Alberto (2013)
This paper examines the value relevance of accounting fundamentals in the Mexican Stock Market ([BMV] – Bolsa Mexicana de Valores). The research question that motivated the paper was: Can accounting fundamentals provide relevant information to better understand firm value? More specifically, the paper examines whether the application of an accounting fundamental strategy to select stocks of a portfolio can systematically yield significant and positive excess market buy-and-hold returns after one and two years of portfolio formation. Based on valuation theory, accounting research and the maturity level of the BMV, a set of accounting fundamental signals is proposed that reflects information that influences security prices, but not necessarily in a timely manner. Using quarterly financial and market data from 196 BMV stocks from 1991 to 2011, it is shown that after controlling for earnings, book-to-market ratio and firm size, the fundamental strategy proposed here provides value information relevant to investors. The relationship between the accounting fundamental signals proposed and the buy-and-hold market future return (one-year and two-year returns) is significant and positive considering the 1991-2011 period. Portfolios formed with high scores of these signals show an average of 1.62% market excess annual return between 1991 and 2011, and about 9% between 1997 and 2011. Besides the practical implication of the findings –e.g. the possibility mispriced securities– this paper contributes to the scarce accounting research in Latin American capital markets by furthering understanding of the “post-earnings” drift phenomenon in the BMV.